2016
DOI: 10.21037/jtd.2016.09.63
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salivary aspiration using radionuclide salivagram SPECT/CT in patients with COPD exacerbation: a preliminary study

Abstract: Background: The aim of this prospective study was to assess the utility of radionuclide salivagram for detecting salivary aspiration in AECOPD patients and to evaluate the adding value of SPECT/CT to planar Conclusions: Radionuclide salivagram is an objective method for detecting salivary aspiration in AECOPD patients. Moreover, SPECT/CT can identify more precise location of salivary aspiration and suggest a possible role for saliva in the pathophysiology of aspiration pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Dysphagia was examined by the Eating Assessment Tool-10 (EAT-10) [ 27 ] and the 30mL Water Swallow Test (WST) [ 28 ]. In the present study, dysphagia was considered to be present if the results of both tools indicated dysphagia.…”
Section: Methodsmentioning
confidence: 99%
“…Dysphagia was examined by the Eating Assessment Tool-10 (EAT-10) [ 27 ] and the 30mL Water Swallow Test (WST) [ 28 ]. In the present study, dysphagia was considered to be present if the results of both tools indicated dysphagia.…”
Section: Methodsmentioning
confidence: 99%
“…Radionuclide techniques have been described and studied in the past, mostly in children, in an attempt to increase the sensitivity of the detection of aspiration. The study is performed by mixing technetium‐99m sulfur colloid with milk or water, followed by delayed imaging up to 24 h 8,9 . Although these tests provide objective diagnostic tools in the diagnosis of aspiration pneumonia, they are not used frequently in clinical practice.…”
Section: Aspiration Pneumoniamentioning
confidence: 99%
“…14 Oro-pharyngo-esophageal radionuclide scintigraphy (OPERS) is an investigation that is currently done using a radionuclide salivagram to evaluate swallowing and pulmonary aspiration in children and adults. [15][16][17][18] Radionuclide scintigraphy not only detects penetration and aspiration, but also quantifies the amount of food material that enters the chest after swallowing. 19,20 However, there is a paucity of studies reporting on the application of OPERS in the evaluation of aspiration related to dysphagia.…”
Section: Introductionmentioning
confidence: 99%